KEPATUHAN TENAGA KESEHATAN TERHADAP STANDAR OPERASIOANAL PROSEDUR PERTOLONGAN PERSALINAN UNTUK MENURUNKAN ANGKA KEMATIAN IBU DI PROVINSI SUMATERA SELATAN - Retnaningsih, Ekowati; Nuryanto, Nuryanto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
The purpose of this study to determine the factors associated with adherence to a person in performing their duties in accordance with the guidelines of the SOP Standard Normal Maternity Care in South Sumatra Province. This study uses a quantitative approach with cross-sectional study design (cross-sectional). The population is the entire health worker / midwife in private practice in the City and County Banyuasin Palembang in South Sumatra Province. Sample health worker / midwife in private practice amounted to 73 people who do the delivery assistance during the study. Quantitative data processing performed using computerized. The results showed 67.1% of health workers who have adhered to run the SOP delivery assistance, the average age of respondents was 40 years old, the youngest age is 22 years old and the oldest was 65 years of age, educational level of most graduate midwifery D-3 is 80.8 %, married status (married) which is about 86.3%, the average income of more than Rp. 4000.000, -, all health workers (100%) received good support from family friends as well. The level of knowledge the respondents 92.8% had good, good attitude of respondents 81.1%, 72.6% have already followed the training of health personnel APN, total 97.3% of health workers already have a health facility and 52.1% said facilities are complete , Motivation of health workers has been a good 63%. There is a significant association between knowledge, attitudes and availability of health facilities with a compliance rate of health workers in carrying out the SOP delivery assistance.